2004
DOI: 10.1016/j.joca.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid levels may have predictive value for the progression of knee osteoarthritis

Abstract: In our study, serum levels of hyaluronic acid and pentosidine had a predictive value for further development of knee OA in that further joint space narrowing was detected in the patients with knee OA in the next 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 29 publications
3
61
1
1
Order By: Relevance
“…Increasing intra-articular HA is then forced into blood and lymph due to increasing intra-articular pressure [21]. Furthermore, HA is a component of cartilage, and radiographic joint-space narrowing by cartilage damage is correlated with higher serum HA levels [13]. On the other hand, it is considered that serum biomarkers are affected by other systemic factors, such as medical problems associated with aging, circadian rhythm, food intake and vigorous activities [15] because data are obtained from blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing intra-articular HA is then forced into blood and lymph due to increasing intra-articular pressure [21]. Furthermore, HA is a component of cartilage, and radiographic joint-space narrowing by cartilage damage is correlated with higher serum HA levels [13]. On the other hand, it is considered that serum biomarkers are affected by other systemic factors, such as medical problems associated with aging, circadian rhythm, food intake and vigorous activities [15] because data are obtained from blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…P value <0.05 significant for this biomarker. Previous reports have suggested that serum HA levels are associated with several joints [5,[7][8][9][10][11][12][13]. In the literature, there is a major focus on the relationship between knee OA and serum HA levels [5,7,[10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These 2 markers have been used in human studies and are shown to be indicative of various aspects of OA. HA is a glycosaminoglycan found in synovium and cartilage that predicts disease outcome in knee (39) and hip OA (40) and correlates with OA progression (39)(40)(41)(42)(43)(44)(45). To date, there are few data regarding serum or synovial fluid biomarker levels following articular fracture and the subsequent development of arthritis.…”
mentioning
confidence: 99%